2019
DOI: 10.1007/s11250-019-02133-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative state in the estrus cycle of the buffaloes: a preliminary study

Abstract: The oxidative status, the relationship between oxidizing agents (free radicals) and antioxidant system, is able to influence the correct performance of the oestrous cycle. The aim of the experimentation was to define a first range of physiological values of reactive oxygen species (ROS) and the biological antioxidant potential (BAP), found during the phases of the buffalo estrous cycle. In this study, blood samples were taken from 30 buffaloes in various phases of the estrous cycle (oestrus, dioestrus, anoestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…The study was performed on 30 healthy buffaloes, of which ten were in estrus, ten in diestrus, and ten in anestrus. The authors found the highest d-ROMs value and the lowest BAP level during the estrus phase, though the d-ROMs and BAP levels reported by the authors were lower than those observed in our study [33]. This finding may be related to the difference in the number of animals analyzed between the studies.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The study was performed on 30 healthy buffaloes, of which ten were in estrus, ten in diestrus, and ten in anestrus. The authors found the highest d-ROMs value and the lowest BAP level during the estrus phase, though the d-ROMs and BAP levels reported by the authors were lower than those observed in our study [33]. This finding may be related to the difference in the number of animals analyzed between the studies.…”
Section: Discussioncontrasting
confidence: 95%
“…In addition, the reference values for these biomarkers have not yet been defined. Recently, a preliminary study reported the physiological range of d-ROMs and BAP levels during the different phases of the estrus cycle in buffaloes [ 33 ]. The study was performed on 30 healthy buffaloes, of which ten were in estrus, ten in diestrus, and ten in anestrus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another point is that, the Hp concentration during estrous phase was significantly higher compared to diestrous and proestrous in non-synchronized estrous cycle in cows ( Samimi et al., 2020 ) , according to its higher production from the reproductive tract around the time of ovulation. What is more, behavioral stress during the ovulation, as the increased oxidative activity and released free radicals across estrous, could be other reasons for the Hp increases ( Sciorsci, Galgano, Mutinati & Rizzo, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, in non-synchronized estrous cycles in cows, haptoglobin (Hp) was significantly higher compared to diestrus and proestrus [ 37 ]. It seems that behavioral stress during ovulation in buffaloes, as increased oxidative activity and free radical release during estrus, could be other reasons for the increase of Hp [ 38 ]. However, Fe metabolism under these inflammatory response conditions was not evaluated in any of these studies.…”
Section: Discussionmentioning
confidence: 99%